The Hamilton Family - Unknown:::Creator::::::::::::
John Steinbeck's maternal family, the Hamiltons, at the home of Olive and John Ernst Steinbeck. Celebrating the golden wedding anniversary of Elizabeth and Samuel Hamilton. Standing, left to right: John Ernst Steinbeck (John Steinbeck's father), Mamie Hamilton (wife of George), Will Hamilton (husband of Adela), Joe Hamilton, Aunt Euna 'Lizzie' Hamilton, Thomas Hamilton, Dessie Hamilton, Will Martin, Mollie Hamilton Martin. Sitting (adults) left to right: Olive Hamilton Steinbeck, George Hamilton, Adela 'Dade' Winkler (Will's wife), Elizabeth Hamilton, Samuel Hamilton. Sitting (children) left to right: Elizabeth Steinbeck, Marian Hamilton (daughter of Mamie and George), Esther Steinbeck. Of these Samuel Hamilton, Uncle Will, Aunt Adela, and Uncle Thom are mentioned in East of Eden. Original is in the safe.